2018
DOI: 10.1177/2150132718776877
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Personality Disorder Cluster on Depression Outcomes Within Collaborative Care Management Model of Care

Abstract: Background: Previous studies have suggested that having a comorbid personality disorder (PD) along with major depression is associated with poorer depression outcomes relative to those without comorbid PD. However, few studies have examined the influence of specific PD cluster types. The purpose of the current study is to compare depression outcomes between cluster A, cluster B, and cluster C PD patients treated within a collaborative care management (CCM), relative to CCM patients without a PD diagnosis. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…32-36 We have also shown that comorbid psychiatric and medical conditions can have a negative impact on depression outcomes at 6 months. 35,37-40 Recently, we reviewed the electronic records of 2826 depressed patients enrolled in CCM and found that current smokers had an associated decreased treatment adherence and worse clinical outcomes at 6 months compared with non-smokers. 41 Therefore, we sought to evaluate whether a current smoking history had a negative impact on depression treatment of adult primary care patients in the context of treatment with UC versus treatment with CCM.…”
Section: Introductionmentioning
confidence: 99%
“…32-36 We have also shown that comorbid psychiatric and medical conditions can have a negative impact on depression outcomes at 6 months. 35,37-40 Recently, we reviewed the electronic records of 2826 depressed patients enrolled in CCM and found that current smokers had an associated decreased treatment adherence and worse clinical outcomes at 6 months compared with non-smokers. 41 Therefore, we sought to evaluate whether a current smoking history had a negative impact on depression treatment of adult primary care patients in the context of treatment with UC versus treatment with CCM.…”
Section: Introductionmentioning
confidence: 99%